Influence Of Organizational Factors And Demographic Variables On Job Satisfaction Among Hotel Employees In Bangladesh - Akter, Afroza (2019)
The present study aims to examine the relationship between organizational factors, demographic variables and employee job satisfaction of hotel employees in Bangladesh. This study followed cross-sectional research design in which questionnaire survey method was employed to collect data. Data for this study included the perceptions of hotel employees of Bangladesh on the relationship among organizational factors (salary, job security, promotion opportunity, working condition, recognition and training and development), demographic variables (Age, gender, marital status and education) and employee job satisfaction.